2021
DOI: 10.3390/cells10020386
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biomarker Analyses of Post-COVID-19 Complications and Neurological Manifestations

Abstract: As the SARS-CoV-2 pandemic continues, reports have demonstrated neurologic sequelae following COVID-19 recovery. Mechanisms to explain long-term neurological sequelae are unknown and need to be identified. Plasma from 24 individuals recovering from COVID-19 at 1 to 3 months after initial infection were collected for cytokine and antibody levels and neuronal-enriched extracellular vesicle (nEV) protein cargo analyses. Plasma cytokine IL-4 was increased in all COVID-19 participants. Volunteers with self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
166
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(181 citation statements)
references
References 57 publications
(79 reference statements)
12
166
1
2
Order By: Relevance
“…86 Although no differences were found between COVID-19 patients with and without reported neurological symptoms, this study confirmed that COVID-19 alters the cargo of neuronal-enriched exosomes, with high levels of toxic proteins that were still found altered in patients who have recovered from COVID-19. 86 Studies correlating these findings in the plasma of COVID-19 patients and their neurological status are underway.…”
Section: Diagnostic Potential Of Exosomes In Covid-19supporting
confidence: 55%
See 3 more Smart Citations
“…86 Although no differences were found between COVID-19 patients with and without reported neurological symptoms, this study confirmed that COVID-19 alters the cargo of neuronal-enriched exosomes, with high levels of toxic proteins that were still found altered in patients who have recovered from COVID-19. 86 Studies correlating these findings in the plasma of COVID-19 patients and their neurological status are underway.…”
Section: Diagnostic Potential Of Exosomes In Covid-19supporting
confidence: 55%
“…86 Interestingly, compared with the historic cohort, all COVID-19 patients had increased protein markers of neuronal dysfunction, such as amyloid β, neurofilament light, neurogranin, total tau, and p-T181-tau. 86 Although no differences were found between COVID-19 patients with and without reported neurological symptoms, this study confirmed that COVID-19 alters the cargo of neuronal-enriched exosomes, with high levels of toxic proteins that were still found altered in patients who have recovered from COVID-19. 86 Studies correlating these findings in the plasma of COVID-19 patients and their neurological status are underway.…”
Section: Diagnostic Potential Of Exosomes In Covid-19mentioning
confidence: 92%
See 2 more Smart Citations
“…Infection with SARS-CoV-2 may also initiate protein aggregation via heparin-binding sites and/or spike-derived peptides, leading to amyloid fibrils that may produce similar pathology to Alzheimer’s disease [ 10 ]. Elevated levels of amyloid-beta, neurofilament light, neurogranin, and tau in patients 1–3 months after recovery from COVID-19 suggest generation of neurotoxic proteins may contribute as well [ 11 ].…”
Section: Introductionmentioning
confidence: 99%